Pengaruh Kemampuan Kerja, Disiplin Kerja Dan Pengawasan Terhadap Kinerja Karyawan Pada PB Swalayan 21 Kota Metro - Deny Edy Widodo; Sri Retnaning Rahayu; Meila Efriyana (Jurnal Manajemen DIVERSIFIKASI, 2024)
This research aims to analyze the influence of Work Ability, Work Discipline and Supervisionon employee performance. This type of research is quantitative research with a population of54 employees registered at PB Swalayan 21 Metro City, only 48 samples used that fit thepredetermined criteria. The data used is secondary data from the distribution ofquestionnaires in the form of a list of questions with several alternative answers forrespondents. The statistical test used to test the hypothesis is a multiple linear regressionanalysis test and tested using the statistics packages for the social science (SPSS) version 21program. Based on the results of the statistical test, it shows that Work Ability, WorkDiscipline, Supervision have a positive and significant influence on performance. employee.